A PHYLOGENETIC ANALYSIS OF THE RBCL GENE SEQUENCE OF THE PLANT GENUS AEGOPODIUM L. (Experimental biology, 2023)
For many diseases, medicinal plants have been used in treatment since ancient times. The relevance of research on medicinal plants is growing day by day. This is due to the fact that the effect of medicinal plants is higher and the effect of chemical drugs is stronger. Currently, there are numerious studies on the effects of medicinal plants and it is proven that they act more sparingly than chemical drugs. In this regard, genetic taxonomic determination will be more effective than morphological identification of medicinal plants. Thanks to the bioinformatics, it is increasingly possible to identify genes isolated from plants, align them with genes in a database, and perform phylogenetic analysis. In our work, DNA was isolated from the leaves of Aegopodium alpestre Ledeb., and the rbcL gene was sequenced, then a phylogenetic analysis was carried out to determine the relationship with Aegopodium L., as well as with representatives of the Umbelliferae family. The study showed that the plant Aegopodium alpestre Ledeb. according to the sequences of the rbcL gene, it is closer to the genus Aegopodium L, in contrast to other representatives of the Apiaceae family. However, between them were not found strong similarities.
Keywords: rbcL, Aegopodium L., Aegopodiumalpestre Ledeb., isolation DNA, phylogenetic analysis